2013
DOI: 10.1177/1362168813494126
|View full text |Cite
|
Sign up to set email alerts
|

How ‘sign meaning develops’: Strategic mediation in learning to teach

Abstract: A fundamental goal of any L2 teacher education program is to move novice teachers toward greater levels of professional expertise, both in terms of what they know and what they can do with what they know. Yet, it is less clear how the activities embedded in teacher education programs actually assist novice teachers as they move toward greater levels of expertise. Informed by a sociocultural theoretical perspective on teacher learning (Johnson, 2009) this study examines the practices of a teacher educator as sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 15 publications
(6 reference statements)
2
25
0
Order By: Relevance
“…The data indicated that despite varying levels of collaboration-seemingly inevitable in any social engagement of this type-team teaching possesses the clear potential to enhance pre-service teacher engagement, provide additional levels of affective support and ultimately provide opportunities for developing higher order learning. These findings confirm previous studies that argue that teacher learning experiences need careful planning that includes activities and tools that support collaborative and dialogic practices (Sorensen, 2014;Johnson& Kuerten Dellagnelo, 2013) In the case of the assistant teaching model presented here, although the experience involved limited participation from the pre-service teachers, they managed to exercise enhanced agency as teachers and collaborated with their own activities and were more motivated to improve their orientation to teaching and learning tasks. In the second instance, the peermentoring model implemented provided a clearly richer potential environment for collaboration.…”
Section: Discussionsupporting
confidence: 88%
“…The data indicated that despite varying levels of collaboration-seemingly inevitable in any social engagement of this type-team teaching possesses the clear potential to enhance pre-service teacher engagement, provide additional levels of affective support and ultimately provide opportunities for developing higher order learning. These findings confirm previous studies that argue that teacher learning experiences need careful planning that includes activities and tools that support collaborative and dialogic practices (Sorensen, 2014;Johnson& Kuerten Dellagnelo, 2013) In the case of the assistant teaching model presented here, although the experience involved limited participation from the pre-service teachers, they managed to exercise enhanced agency as teachers and collaborated with their own activities and were more motivated to improve their orientation to teaching and learning tasks. In the second instance, the peermentoring model implemented provided a clearly richer potential environment for collaboration.…”
Section: Discussionsupporting
confidence: 88%
“…To explore the teaching–learning relationships ( obuchenie ) that unfold in the practices of L2 teacher education, data extracts are presented from an extended team‐teaching project that was embedded in a 15‐week TESOL methodology course (Johnson & Arshavskaya, ; Johnson & Dellagnelo, ; Johnson & Worden, ). The project required a team of four novice teachers to engage in a series of activities designed to prepare them to teach a single lesson in an actual English as a second language (ESL) class.…”
Section: The Extended Team‐teaching Project Participants and Datamentioning
confidence: 99%
“…This lack of theorisation is one of the reasons why there is inconsistency between studies in terms of what constitutes the context. While some researchers consider the context as the community involved in the teaching and learning activity (e.g., Atay, 2007;Brandt, 2006;de Courcy, 2011;Gan, 2013;Trent, 2013;Urzúa & Vásquez, 2008;Yuan & Lee, 2014), others account for the systems of rules (Atay, 2007;Engin, 2014;Gao & Benson, 2012) and pedagogical tools (de Courcy, 2011;Johnson & Dellagnelo, 2013). As what constitutes context of teaching and learning varies from one study to another, it is really challenging to synthesise and compare findings from different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have looked into the rules and policies regulating language teaching and learning and SLTE in specific contexts (e.g., Atay, 2007;Cross, 2006;Cross, 2010;Gao & Benson, 2012). The role of tools and artefacts in mediating teacher learning is also an emerging theme in research on SLTE (de Courcy, 2011;Johnson & Dellagnelo, 2013). The context of SLTE is complex and involves multiple factors.…”
Section: Contemporary Research On L2 Teacher Learning In Light Of Thementioning
confidence: 99%